Discourses of Cultural Continuity among the Bakweri of Mount Cameroon National Park - Nebasifu, Ayonghe Akonwi; Atong, Ngoindong Majory (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2019)
In recent years, the separation of people from their land through protected areas and conservation initiatives of local governance has been at the core of criticism in the people–park discourse. However, vital questions remain as to how people maintain cultural relations to parks and their peripheral zones. This paper explores circumstances where people are not entirely disconnected from their culture despite the state management of Mount Cameroon National Park (MCNP) in West Africa. In this example, people uphold subsistence activities and spiritual interaction with ancestors and deities steered under the umbrella of ritual beliefs. Based on an ethnographic inquiry among the Bakweri in the southwest region of Cameroon, we found that factors of remote settlement, an urge for collective assurances among people, and a sense of belonging in an ethnic group enhance a reciprocal attachment between people and place. This observation helps bridge gaps in people–park relations through cultural continuity.